Análisis del sistema fonológico segmental del malecu con base en descripciones anteriores - Krohn, Haakon S. (2023)
This paper is an analysis of the segmental phonological system of Maleku (Guatuso) on the basis of previously published phonological and phonetic descriptions. It has a particular focus on the distinctive features that contrast the phonemes, since no other publication has addressed this topic in detail before. In the patrimonial consonantal system, a total equivalence is established between the values of the features [sonorant] and [voice] if the phoneme classified as a voiced palatal fricative is considered a “sonorant fricative”. On the other hand, in the innovative system, which incorporates four phonemes borrowed from Spanish, the contrastivity of the feature [voice] is activated due to the introduction of voiced stop phonemes that contrast with the unvoiced stops.